A rare case of low transverse vaginal septum - Singh, Sanjay; Biswas, Manash; Dey, Madhusudan; Nambula, Vijayalakshmi; Abbas, Fatima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Transverse vaginal septum is a rare cause of genital outflow tract obstruction. It results from incomplete fusion/recanalization between the vaginal components of the mullerian ducts and the urogenital sinus. The septum varies in thickness and may be present anywhere along the vagina, although most are found in the upper and mid-vagina. A complete septum results in primary amenorrhoea and several short term and long term sequelae including endometriosis and infertility. We present a case of 12-year old girl who presented with intermittent, colicky abdominal pain. She had undergone low anorectoplasty at 18 months of age. She had not yet attained menarche. Secondary sexual characters were appropriately developed. The clinical examination revealed a small, blind ending lower vagina and a tender, bimanually palpable mobile mass in the suprapubic region. The ultrasound examination revealed fluid collection with internal echoes within the endometrial cavity extending into the upper vagina. The magnetic resonance imaging of pelvis confirmed the thickness (four cm) and location of the transverse vaginal septum (lower one third) along with presence of hematocolpos in upper 2/3rd of the vagina, hematometra and hematosalpinx. She underwent successful excision of the septum. Amnion was used for the epithelialisation of the denuded vaginal mucosa.